1994
DOI: 10.1002/jcb.240550206
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin promotes differentiation of osteoclast progenitors from murine long‐term bone marrow cultures

Abstract: Murine long-term bone marrow cultures (LTBMCs) were used to generate hematopoietic cells free from marrow stromal cells. These progenitor cells were treated with GM-CSF (5 U/ml) with or without rat bone osteocalcin or rat serum albumin in either alpha-MEM with 2% heat-inactivated horse serum alone (alpha) or supplemented with 10% L-cell-conditioned medium (as a source of M-CSF) (L10). Few substrate-attached cells survived in basal alpha medium, but when treated with L10 medium or GM-CSF, they survived and prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 35 publications
(23 reference statements)
0
20
0
1
Order By: Relevance
“…collagen type I) and non-collagenous bone matrix proteins, like osteocalcin (OC), bone sialoprotein (BSP), osteopontin (OPN) or growth factors like bone morphogenetic proteins (BMP) to modify the cements [10][11][12][13][14][15]. These compounds are known to be very effective in stimulating bone cell activity and bone healing [16][17][18][19][20][21][22]. Furthermore, these molecules are able to support a bone like HAP morphology [21][22][23][24][25][26][27], mostly because of specific peptide sequences and functional substituents like phosphate and carboxylic groups.…”
Section: Introductionmentioning
confidence: 98%
“…collagen type I) and non-collagenous bone matrix proteins, like osteocalcin (OC), bone sialoprotein (BSP), osteopontin (OPN) or growth factors like bone morphogenetic proteins (BMP) to modify the cements [10][11][12][13][14][15]. These compounds are known to be very effective in stimulating bone cell activity and bone healing [16][17][18][19][20][21][22]. Furthermore, these molecules are able to support a bone like HAP morphology [21][22][23][24][25][26][27], mostly because of specific peptide sequences and functional substituents like phosphate and carboxylic groups.…”
Section: Introductionmentioning
confidence: 98%
“…[5,[7][8][9] Besides anemia, lead-induced enzymatic inhibition causes a range of other pathologies. One can quote, for example, the replacement of calcium by lead in synaptogamin [5,10] or osteocalcin (bone Gla protein), [11][12][13] which induces nervous system aftereffects or delays osseous growth, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also suggested a role for osteocalcin as a matrix signal for the recruitment and differentiation of osteoclasts (18)(19)(20)(21). However, the understanding of the physiological function of osteocalcin was substantially advanced when a model for osteocalcin gene deficient mice was generated through mouse genetics (22).…”
mentioning
confidence: 99%